2010
DOI: 10.1007/s11999-009-1226-7
|View full text |Cite
|
Sign up to set email alerts
|

Hinged Total Knee Arthroplasty in the Presence of Ligamentous Deficiency

Abstract: Background Rotating-hinge total knee prostheses may be used for the treatment of global instability about the knee. The designs of previous generations were associated with suboptimal outcomes. Questions/purposes We evaluated the clinical and radiographic outcomes of salvage knee reconstructions using modern-generation, modular, kinematic rotating-hinge total knee prostheses. Methods We retrospectively reviewed 26 rotating-hinge arthroplasty devices to examine whether acceptable results were obtainable using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 18 publications
2
42
0
2
Order By: Relevance
“…Clinical studies of modern-generation rotating-hinge prostheses have been reported by numerous authors [2,6,9,[13][14][15][16]. Numerous authors have reported improvements in pain and function [2,9,10,13] and ROM [10,15] after the use of rotating-hinge prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies of modern-generation rotating-hinge prostheses have been reported by numerous authors [2,6,9,[13][14][15][16]. Numerous authors have reported improvements in pain and function [2,9,10,13] and ROM [10,15] after the use of rotating-hinge prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reports of reduced pain and improved ROM, Knee Society scores, and patient satisfaction after the use of modern-generation rotatinghinge prostheses in complex revision situations [1,6], medium-and long-term followup is limited [2,6,9,13,14,16] and some authors continue to report complications and failures related to aseptic loosening, infection, and periprosthetic fracture with these devices [14,19]. None of these described failures of the hinge mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional lengthening or partial release of the superficial MCL at the tibial attachment [1,26] carries the risk of inadvertent rupture or complete detachment of the ligament. Complete release of the superficial MCL from its tibial attachment, with or without reattachment [9,11,12], is an imprecise technique that simultaneously increases the medial gap in extension and flexion [16], leading to potential medial instability or laxity. For surgeons balancing the flexion gap by placing the AP cutting block parallel to the tibial cut, it would require internal rotation of the femoral component to balance the flexion gap medially, with possible adverse consequences for patellar tracking [8].…”
Section: Discussionmentioning
confidence: 99%
“…For surgeons balancing the flexion gap by placing the AP cutting block parallel to the tibial cut, it would require internal rotation of the femoral component to balance the flexion gap medially, with possible adverse consequences for patellar tracking [8]. Lastly, constrained implants in such complex varus deformities have been reported to give good short-and intermediate-term functional outcomes and survival rates after primary TKA [3,9,11,13,14]. However, in view of the prohibitive cost involved and complexity of revision surgery if required, we reserve constraint implants only for arthritic knees with complex deformities associated with substantial instability, especially in elderly, sedentary patients [9,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation